THE ROLE OF THIRD PARTY SUPPORTED FOR DETERMINING CUSTOMERS ADOPTION OF INTERNET BANKING - ChyadAlkafagi, Alaa Ahmed; Romli, Ruslan Bin; Bahaudin, Ahmad Yusni Bin; Alekam, Jamal Mohammed (International Journal of Research -GRANTHAALAYAH, 2015)
Definitely the Internet banking services adoption (IBSA) represents a good opportunity for developing nations to attain greater economic development and growth. This sector plays a vital role in developing numerous businesses and increasing Gross Domestic Product (GDP) in different countries, particularly in developing countries, such as the Republic of Iraq. Although a lot of research evidences the wide adoption of Internet banking in developed nations, there is still limited research in developing nations in the Middle East, specifically in Iraq on this area. There is definitely a need in this country to identify the factors that could encourage IBSA. There is also a paucity of empirical research on IBSA from the perspective of customers. Taking these into cognizance, this quantitative research aims to understand IBSA, by investigating the key factors that encourage customers to adopt Internet banking in the Iraqi context, using the Theory of Planned Behavior (TPB). In order to test this framework, a quantitative approach using the survey method is employed consisting of twenty eight (28) items with a seven-point Likert scale. Based on proportionate stratified random sampling, 535 out of 800 employees. For analysis purposes, Partial Least Squares-Structural Equation Modeling (PLS-SEM) was applied. Findings of this study reveal that all the research hypotheses are supported except one, namely subjective norms. This study found out there is high impact the role of third party support toward Internet banking services adoption among Iraqis customers.